CONDITIONS OF EFFECTIVE FORMATION COMMUNICATIVE CULTURE OF STUDENTS BY MEANS EXTRACURRICULAR WORK - O.O. Havrylyuk (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the problem of pedagogical conditions of effective forming students' communicative culture by means of extracurricular activity in higher pedagogical school.